Generalized proportional integral observer–based composite control method for robotic thermal tactile sensor with disturbances. (6th June 2017) - Chen, Congyan; Wang, Yanduo; Li, Shihua
In this article, we discuss the temperature regulation problem of robotic thermal tactile system under unknown time-varying disturbances. In order to improve the disturbance rejection property of the thermal system, a composite controller is presented. First, a generalized proportional integral observer is introduced to estimate the system disturbances, which generally include model uncertainties and external disturbances. Second, a feedback control is designed using feedback linearization control technique. A composite temperature controller is obtained as a composition of feedback linearization–based controller plus feed-forward compensation based on generalized proportional integral observer. A rigorous analysis shows that the proposed scheme can enhance the disturbance rejection property of the thermal system. Simulation and experimental comparisons with two other control methods, that is, the composite control method with feedback linearization–based control plus feed-forward compensation based on disturbance observer and the proportional integral control method, are given to verify that the proposed method exhibits a much better disturbance rejection performance.